2018
DOI: 10.1007/s10549-018-4685-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel patient-derived xenograft model for claudin-low triple-negative breast cancer

Abstract: Here, we characterize a claudin-low TNBC patient-derived xenograft model that can be utilized for therapeutic research studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…However, because genomic differences in TU-BcX- 2O0 treated explants most recapitulated cell line effects compared to our other TNBC models, we chose to interrogate TU-BcX-2O0 as the translational model in this study. We have previously described TU- BcX-2O0 as a claudin-low TNBC PDX model [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because genomic differences in TU-BcX- 2O0 treated explants most recapitulated cell line effects compared to our other TNBC models, we chose to interrogate TU-BcX-2O0 as the translational model in this study. We have previously described TU- BcX-2O0 as a claudin-low TNBC PDX model [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dissecting the various aspects of PDX breast tumors provides the ideal model to study how HDAC inhibitors, or other small molecule inhibitors, affect different microenvironment components in a translational setting. In our investigation, we utilize a novel CL-TNBC PDX model established in our laboratory [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PDX breast cancer models are being deployed in studies evaluating tumor drug response at the physiological and transcriptomic levels. 13,[43][44][45] Nevertheless, the logistics of tissue processing and storage within a relatively short time frame are roadblocks to the widespread adoption of PDX as an avenue for individualized medical therapy and patient stratification in clinical trials.…”
Section: Breast Cancer Cells and 3d Modelsmentioning
confidence: 99%
“…3,10 While there have been recent advances in the generation of patientderived xenograft (PDX) models, these continue to require immunodeficient mice as in vivo hosts for both expansion and propagation-based studies. [11][12][13] Studies have shown that both the ECM and murine host system impact the pathophysiology of human-derived breast cancer cells, thereby demonstrating a need for an alternative approach that is less dependent on the mouse. 14,15 Based on the principles introduced by Bissell, Griffith, Prestwich, and their colleagues, [4][5][6]16,17 an ideal human breast cancer MPS model would possess the above characteristics regarding performance consistency, ease of use, and amenability to highthroughput formats, in addition to the following attributes:…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lehmann et al have proposed four TNBC tumor specific subtypes referred to as basal like (BL)1, BL2, mesenchymal and luminal androgen receptor (LAR) ( 80 ). Basal-like tumors that are triple negative and have low expression of luminal differentiation markers, high expression of genes involved with the epithelial-to-mesenchymal transition (EMT) and immune response, and are enriched with cancer stem cells are referred to as claudin-low (CL) TNBC ( 81 ). One study demonstrated supplementation with EPA+DHA (0.025%) significantly decreased growth of models of both claudin low (CL) and basal-like (BL) murine mammary tumors in mice fed an obesogenic diet (60% fat) ( 48 ).…”
Section: Fish Oil and Tnbc: Reviewmentioning
confidence: 99%